Spatial pattern of tourist attractions and its influencing factors in China. Issue 2 (3rd May 2020) - Wang, Ting; Wang, Lu; Ning, Zhi-Zhong
ABSTRACT: Based on the location data of 9820 A-grade tourist attractions in China, this study adopts the nearest-neighbour distance method, multi-distance clustering and kernel density analysis to study the distribution pattern of scenic spots and their relationship with natural and socio-economic factors. The spatial pattern of Chinese tourist attractions is found to be an aggregate. The spatial pattern of tourist attractions varies by their grade: China's tourist attractions are mainly distributed in plains and basins, close to main water systems. They are also distributed in areas with dense population and high levels of economic development, urban agglomeration and transport infrastructure.